2020
DOI: 10.3390/ijerph17082874
|View full text |Cite
|
Sign up to set email alerts
|

What Keeps Them Physically Active? Predicting Physical Activity, Motor Competence, Health-Related Fitness, and Perceived Competence in Irish Adolescents after the Transition from Primary to Second-Level School

Abstract: Physical activity (PA) decreases with age. The school transition is noted for significant changes in PA behaviour. Motor competence (MC), health-related fitness (HRF), and perceived competence (PC) are generally positively associated with PA. The aim of this study was to examine longitudinal cross-lagged relationships between PA, MC, HRF, and PC across the school transition from final year of primary school to first year of second-level school in Irish youth. PA (accelerometery), object-control and locomotor M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 72 publications
(115 reference statements)
3
31
1
3
Order By: Relevance
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…An agreed understanding of how the transition period from elementary to secondary school affects PA remains sparse, as the environments (school, family, peer, intrapersonal) adolescents experience vary drastically around the world [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In a previous qualitative study, girls’ participation in PA during the transition was related to the change in PA opportunities, decreased social support from friends and families to be active, increased pressure to be skilled in order to participate in PA, and competing priorities that took them away from PA [ 16 ]; however, changes like this are not as prevalent when regular MVPA is mandated in the school’s curriculum [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of research has confirmed the various hypotheses generated in Stodden's model [9] at early [3,[10][11][12][13], middle [3,5,13,14], and late childhood [3,10,13,[15][16][17], and to a limited extent, into adolescence [18][19][20]. In general, research in adolescent populations suggests that their physical activity levels are significantly influenced by HRF and PMC; specifically, higher physical activity levels are achieved in adolescence when individuals are highly fit and have high perception of motor competence in childhood [18,20]. MC and HRF are also significantly associated in adolescence, further creating a need to explore these interrelationships in older populations [19].…”
Section: Introductionmentioning
confidence: 89%